The supplier perspective: Forging strong partnerships with buyers - (:unkn) unknown (Emerald Group Publishing Ltd., 2015)
[No abstract available]
Keywords: Automotive industry; Buyer-supplier relationships; Clothing industry; Corporate social responsibility; Germany; Social audits; Strategic partnerships; Turkey